Effect of visual condition and physical activity on the plantar pressure distribution in adult and older women - Hadassa Costa Sousa; Martina Estevam Brom Vieira; Mariana Ferreira Moreira; Juliane Leite Orcino; Darlan Martins Ribeiro; Guilherme Augusto Santos Bueno; Thiago Vilela Lemos; Cibelle Kayene Martins Roberto Formiga; Flávia Martins Gervásio (Universidade Federal de Santa Catarina, 2021)
The aging process causes changes in the physical and functional conditions, as well as in the foot structure and function. This study aimed to analyze the plantar pressure variation with respect to visual information and physical activity in adult and older women. This was a cross-sectional study that included 142 women (mean age of 67.8 years). Participants responded the anamnesis questionnaire, Mini Mental State Examination, and International Physical Activity Questionnaire. Plantar pressure was assessed using computerized baropodometry. Weight distribution was observed in semitandem positions for the right foot forward  and then the left foot forward . Data analysis showed that foot type had no correlation with age (p = 0.37 right foot; p = 0.93 left foot) or level of physical activity (p = 0.28 right foot; p = 0.96 left foot). Moreover, plantar pressure variation showed no significant relationship with age (R2 = 0.2; p = 0.6). In conclusion, plantar pressure variation is not associated with the morphological foot type in women analyzed, as the visual condition did not generate plantar pressure variations when compared to its effect on the classification of plantar arches. Furthermore, level of physical activity was not  associated with plantar pressure variation.